Observational Management of CIN 2 in Young Women: A Prospective Multicenter Trial. Issue 4 (October 2016) - Sykes, Peter; Innes, Carrie; Harker, Dianne; Whitehead, Martin; van der Griend, Rachael; Lawton, Beverley; Hibma, Merilyn; Fitzgerald, Peter; Dudley, Narena; Petrich, Simone; Faherty, Jim; Bergzoll, Cecile; et al.
Abstract : Objectives: We present the rationale and methods for PRINCess—a multicenter prospective trial—which aims to determine outcome and predictors of regression in a large cohort of women younger than 25 years with cervical intraepithelial neoplasia grade 2 (CIN 2) undergoing observational management. Materials and Methods: Six hundred women younger than 25 years with newly diagnosed biopsy-proven CIN 2 are being recruited to observational management (i.e., repeat colposcopy, cytology, and cervical biopsy every 6 months for 2 years). Five hundred fifty-two women from throughout New Zealand and 1 site in Australia have been recruited so far. Measures include histology, cytology, human papillomavirus genotyping, and immunohistochemical staining. Women who develop CIN 3 will be treated with large loop excision of the transformation zone. The primary outcomes are rates of clinical regression of CIN 2 (i.e., 2 consecutive colposcopy follow-ups showing CIN 1 or normal), loss to follow-up, and progression to invasion. Conclusions: The optimal treatment for young women with a diagnosis of CIN 2 is controversial. Although many undergo surgical treatment, observational management is increasingly recommended. However, there is little evidence from large clinical trials of the safety and practicality of observational management of young women with CIN 2. When completed, we will have adequate evidence by which to counsel women regarding their likely outcomes and to offer advice on clinical follow-up protocols. Abstract : A prospective multicenter trial of observational management of CIN 2 in women younger than 25 years.